Konsep Jiwa dan Pengaruhnya dalam Kepribadian Manusia (Studi atas Tafsi>r al-Mishba>h Karya Quraish Shihab) - Hasbi, Muhammad (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2016)
This article attempts to explore Qur’anic notion on soul and its influence on human personality as Quraish Shihab constructed in his Tafsi>r al-Mishba>h. Using psychological and semantical approaches, it parallelizes psychological with Qur’anic perspectives on the concept of soul. Then, it examines how the soul influences human personality. This paper concludes the following. First, Quraish Shihab’s view of the concept of soul can be understood by explaining his thought on the basic concept of human, psychical structure, and human behavioral motivation. Quraish Shihab said that humans’ basic character is kindness. The psychical structure consists of al-fit}rah, al-nafs, al-qalb, al-ru>h, al-‘aql. Then, human behavioral motivation is to complete their physical/biological needs and/or spiritual needs. Second, the soul influences and shapes human personality through integration process among those psychical dimensions.Key Words: konsep jiwa, fit}rah, nafs, qalb, ru>h, ‘aql, integrasi, kepribadian, dan paralelisasi.